The limit of detection in differential scanning calorimetry - Wies, Stefan; Geyer, Andreas; Eysel, Walter (Journal of thermal analysis and calorimetry, 1992)
A procedure is described to determine the limit of detection of DSC instruments by using tiny signals from spontaneous polymorphic transitions of CsCl, K2Cr2O7 and Na2SO4. It is shown how such signals can be found well-resolved in DSC diagrams of powder samples. To distinguish them from the baseline noise they should exhibit a height at least twice that of the baseline width. For the instrument employed the corresponding smallest amount of heat, i.e., the limit of detection, was found to be 0.1 mJ.
Gesehen am 14.03.2023